Foliar resistance to simulated extreme temperature events in contrasting plant functional and chorological types - Gurvich, Diego Ezequiel (2002)
We analysed leaf resistance of 41 Angiosperms belonging to a wide range of plant functional (PFTs) and chorological types (PCTs) to simulated frost and high-temperature extreme events (EE). Leaf resistance was estimated as percentage of membrane electrolyte leakage under heating and freezing treatments in the lab. Leaf resistance to heating or freezing was not significantly correlated with the main resource-use characteristics that defined PFTs, such as leaf specific area, toughness, N concentration or thickness. Leaf resistance to heating differed among PFTs (graminoids and bromeliads were the more resistant groups), but not among PCTs. In contrast, leaf resistance to freezing significantly differed among PCTs. Along a steep regional climatic gradient, climate variables (annual mean temperature, mean minimum temperature, mean maximum temperature and number of frost-free months) at the locations where the given species were most abundant were also significantly correlated with freezing resistance. Species from colder habitats both at the sub-continental and regional scales showed the highest leaf resistance to freezing. Our work indicates that leaf resistance to climatic EE and resource-use strategy (assessed in previous studies) represent two different, partially decoupled axes of plant specialisation. It also suggests that changes in the frequency of very low temperature events might have regional-scale impacts on vegetation, whereas changes in the frequency of very high temperature events might have more influence at the local scale.